Manajemen Pembelajaran PAI pada Masa Pandemi di SMK Ma’arif 1 Kebumen Tahun 2020/2021 - Agus Salim Chamidi (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
Abstract This collaborative research by student-lecturers aims to find out the management of Islamic Religious Education (PAI) learning during the covid19 pandemic at SMK Maarif 1 Kebumen, the obstacles that arise, and the solution steps. This research is a qualitative research using SWOT analysis. Data mining techniques with the methods of interview, observation, and documentation. Research informants are the PAI teachers from grades X, XI, and XII. In addition, other informants were the principal and vice principal of the curriculum field. The research was carried out for two months during PLP activities at the research location. The results of the study are, that (1)learning planning is made with an online learning model, and there are two types of planning, namely, document form and non-document form, (2)the implementation of PAI learning at SMK Ma'arif 1 Kebumen using a blended learning model, (3) obstacles that arise and solutions occur and are divided into two parts, namely, from educators and students.